Implementação e avaliação de uma arquitetura de rede sem fio com topologia baseada em árvore - Guarese, Giuliano Bruno Martins (2014)
The growing demand for wireless equipment for use in industrial automation communication networks has motivated the development of this dissertation. The emergence of new wireless technologies such as Wireless Hart, ISA 100.11a and Zigbee, all based on the IEEE 802.15.4 protocol, as well as the involvement of the author in the development of two wireless products for use in industrial automation, has grounded the area to be searched. This research was restricted in the implementation and evaluation of a wireless network architecture based on tree network topology. This architecture will be exploited for use in industry, in which will be researched and developed based on the IEEE 802.15.4 protocol, today considered the most suitable for industrial automation. This dissertation will look at the research conducted in wireless sensor networks for use in industrial automation systems, as well as the development of a hybrid solution that encompasses one of the most widespread protocols of communication networks in industrial automation, the Modbus RTU protocol, and the IEEE 802.15.4 protocol. This solution involves gateways devices that interface between protocols and create a wireless network with tree network topology as well as end devices that operate with battery and have temperature and humidity sensors. The work covers everything from research and development of the solution, until the final test to validate the developed solution.